Low-lying magnetic excitations and magnetocaloric effect of molecular magnet K6[V15As6O42(H2O)] · 8H2O. (28th October 2015) - Fu, Zhendong; Xiao, Yinguo; Su, Yixi; Zheng, Yanzhen; Kögerler, Paul; Brückel, Thomas
Abstract: Low-temperature heat capacity measurements were performed on the molecular nanomagnet (V15). The low-lying magnetic excitations are clearly evidenced by the Schottky anomalies in the specific-heat data. The energy levels determined from the low-temperature observables agree well with the three-spin model for V15. The magnetocaloric effect of V15 is examined. The maximum entropy change of is found for a field change of at . In spite of the low ground-state spin of V15, a drastic entropy change of is observed for a field change of at 0.4 K, which is comparable to the entropy change of some high-spin sub-kelvin magnetic coolers at such low temperatures. Anisotropy and consequent zero-field splitting result in this characteristic of V15 and may open new possibilities in the design of ultra-low-temperature molecular coolers.